Sailing the boat together: Co-creation of a model for learning during transition. (1st February 2023) - Suliman, Shireen; Könings, Karen D.; Allen, Margaret; Al-Moslih, Ayad; Carr, Alison; Koopmans, Richard P.
Abstract: Purpose: Medical students' transition to postgraduate training, given the complexity of new roles and responsibilities, requires the engagement of all involved stakeholders. This study aims to co-create a transition curriculum and determine the value of involving the key stakeholders throughout such transition in its design process. Methods: We conducted a mixed-methods study involving faculty/leaders (undergraduate/postgraduate), final-year medical students, and chief residents. It commenced with eight co-creation sessions (CCS), qualitative results of which were used to draft a quantitative survey sent to non-participants, followed by two consensus-building CCS with the original participants. We applied thematic analysis for transcripts of all CCS, and mean scores with standard deviations for survey analysis. Results: We identified five themes: adaptation, authenticity, autonomy, connectedness, and continuity, embedded in the foundation of a supportive environment, to constitute a Model of Learning during Transition (MOLT). Inclusion of various stakeholders and optimizing their representation brought rich perspectives to the design process. This was reinforced through active students' participation enabling a final consensus. Conclusions: Bringing perspectives of key stakeholders in the transition spectrum enriches transition curricula. The proposed MOLT can provide a guide for curriculum designers to optimize the final year of undergraduate medical training in preparing students for postgraduate training with essential competencies to be trained.